Subordinate perceptions of the superior and agency costs: Theory and evidence - Douthit, Jeremy; Majerczyk, Michael (Accounting, Organizations and Society, 2019)
This study investigates the effect of subordinate perceptions of the legitimacy of the superior in her role on subordinate misreporting. Using social norm theory regarding property rights, we predict that when subordinates perceive a superior as having more role legitimacy, they perceive the superior as being a more rightful claimant of project profits, which reduces misreporting. We test this prediction using a participative budgeting experiment that manipulates perceptions of the superior's role legitimacy. We find that budgetary slack is lower when subordinates perceive superiors to be legitimate in their roles than when subordinates perceive superiors to be illegitimate. Further, comparisons to a baseline treatment intended to induce neutral perceptions of role legitimacy, as in prior research, suggest that superior role legitimacy decreases slack. Supplemental experiments suggest that these results are generally robust to several design choices. The results from our three experiments suggest that role legitimacy decreases slack relative to random (neutral) perceptions; however, we do not find a statistically significant increase in slack from role illegitimacy relative to random perceptions across our three experiments. We discuss methodological implications from focusing on promoting role legitimacy and implications for practice, which has largely focused on problems from, and avoidance of, illegitimacy.